Age-related waning of immune responses to BCG in healthy children supports the need for a booster dose of BCG in TB endemic countries. Issue 1 (December 2018) - Whittaker, Elizabeth; Nicol, Mark; Zar, Heather; Tena-Coki, Nontobeko; Kampmann, Beate
Abstract In the absence of a more effective vaccine against TB and in the interest of developing one, it is essential to understand immune responses associated with BCG protection. We comprehensively characterized T cell populations in BCG-vaccinated children over time. Blood from 78 healthy, BCG-vaccinated children representing four age groups (<1 yr, ≥1 yr <2 yr, ≥2 yr <5 yr, ≥5 yr), was stimulatedin vitro for 24 hours and 6 days with live BCG to induce effector and central memory responses. Antigen-specific CD4, CD8, γδ and regulatory T cell populations were phenotyped and intracellular and secreted cytokines measured by flow cytometry and multiplex ELISA respectively. Our results demonstrated that populations of naïve T cells predominated in infants, compared to older children. However, BCG-specific effector CD4 T cell responses were equivalent and antigen-specific CD4 T cell proliferative capacity was increased in infants compared to older children. Increases in innate immune responses including γδ T cell responses and secreted pro-inflammatory cytokines were noted with increasing age. In conclusion, we identified that the capacity to expand and differentiate effector T cells in response to BCG stimulation wanes with increasing age, which may indicate waning central memory immunity. Booster vaccination could be considered to maintain the antigen-specific central memory pool and possibly enhance the duration of protection.